Genetic and Shared Environmental Influences on Interferon-g Production in Response to Mycobacterium tuberculosis Antigens in a Ugandan Population - Tao, Li; Zalwango, Sarah; Chervenak, Keith; Thiel, Bonnie; Malone, LaShaunda L.; Feiyou, Qiu; Mayanja-Kizza, Harriet; Boom, Henry; Stein, Catherine M. (The American Society of Tropical Medicine and Hygiene, 2010)
Interferon-g (IFN-g) is a key cytokine in the immune response to Mycobacterium tuberculosis (Mtb). Many studies established IFN-g responses are influenced by host genetics, however differed widely by the study design and heritability estimation method. We estimated heritability of IFN-g responses to Mtb culture filtrate (CF), ESAT-6, and Antigen 85B (Ag85B) in 1,104 Ugandans from a household contact study. Our method separately evaluates shared environmental and genetic variance, therefore heritability estimates were not upwardly biased, ranging from 11.6% for Ag85B to 22.9% for CF. Subset analyses of individuals with latent Mtb infection or without human immunodeficiency virus infection yielded higher heritability estimates, suggesting 10–30% of variation in IFN-g is caused by a shared environment. Immunosuppression does not negate the role of genetics on IFN-g response. These estimates are remarkably close to those reported for components of the innate immune response. These findings have implications for the interpretation of IFN-g response assays and vaccine studies.
Keywords: Genetic; Environmental Influences; Production; Mycobacterium tuberculosis Antigens; Ugandan Population